Reconstructing spruce budworm outbreak severity: a comparison of paleoecological and tree-ring signals - Marc-Antoine Leclerc; Martin Simard; Hubert Morin (PLoS ONE, 2025)
Applying a centennial or millennial perspective to disturbance regimes permits an understanding of how these events have varied in the past in relation to climate change. Correctly interpreting this variability is crucial when preparing sustainable forest management practices for future warming. The eastern spruce budworm (Lepidoptera) is the most important biotic disturbance in the eastern Canadian boreal forest. Adult moths are covered by chitinous scales, and lepidopteran scale records in lake sediments have been analyzed to reconstruct Holocene spruce budworm populations. However, the magnitude of these scale accumulations has yet to be calibrated using an independent proxy. Here, we determine whether the impacts of spruce budworm defoliation are recorded by both sedimentary lepidopteran scale accumulations and tree-ring widths. Agreement between proxies was found at five of nine sites and strongest between the proportion of affected trees and scale accumulations while agreement in signal synchronicity was found at six of nine sites and strongest when comparing scale accumulations to a growth suppression index. A species-based composite chronology relying on white spruce produced the clearest outbreak record for both proxy records. Peak scale accumulations correlated well with smaller tree-ring widths, demonstrating that larger scale accumulations correspond to more severe defoliation events. Therefore, lepidopteran scales provide reliable records of spruce budworm abundance serving as a proxy record ameliorating our understanding of how budworm impacts have fluctuated at centennial and millennial time scales in the context of past climate change.